Dissipation kinetics and the pre-harvest residue of chlorantraniliprole in pigeon pea Cajanus cajan L. succulent pods Using Ultra-High-Performance Liquid Chromatography with Photodiode array detector (UHPLC-PDA) - Murali Krishna T; Devaki K; Kiran Kumar K; Prasanthi L (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2022)
Studies were conducted to evaluate insecticide residues of Chlorantraniliprole in pigeon pea succulent pods after foliar application. Chlorantraniliprole was sprayed at 0.6ml/l on pigeon pea crop at the pod formation stage to control pod borers like Helicoverpa armigera and Maruca vitrata. Samples were drawn at 0, 1, 5, 10, 15, 20, 25, and 30 days after spray. A validated liquid chromatography method with a Photodiode Array (PDA) detector was used for the residue analysis of chlorantraniliprole. Separation was achieved through the C18 column in the reverse phase. The calibration graphs of chlorantraniliprole in acetonitrile solvent or five blank matrices were linear within the tested interval of 0.1 to 1ppm with a coefficient of determination over 0.9990. Dissipation of chlorantraniliprole was studied in first-order kinetic models (for which the coefficient of determination, R2 was 0.8684). Residues of chlorantraniliprole was 3.57, 3.16, 1.61, 1.13, 0.49, 0.21, 0.05 and 0.00mg/kg at 0, 1, 5, 10, 15, 20, 25 and 30 days after spraying. The residue level reached below the tolerance limit (MRL) (2mg/kg BW) of Codex Alimentarius Commission (CAC) on Pesticide Residues after 5 days of spray and below the detectable level after 25 days of spray in succulent pods and recorded a biological half-life of 4.36 days.